IDH1R132H mutation causes a less aggressive phenotype and radiosensitizes human malignant glioma cells independent of the oxygenation status. Issue 3 (September 2015) - Kessler, Jacqueline; Güttler, Antje; Wichmann, Henri; Rot, Swetlana; Kappler, Matthias; Bache, Matthias; Vordermark, Dirk
Abstract Background and purpose In malignant glioma the presence of the IDH1 mutation (IDH1R132H) is associated with better clinical outcome. However, it is unclear whether IDH1 mutation is associated with a less aggressive phenotype or directly linked to increased sensitivity to radiotherapy. Material and methods We determined the influence of IDH1R132H mutant protein on proliferation and growth in 3D culture, migration, cell survival and radiosensitivity in vitro under normoxia (21% O2) and hypoxia (<1% O2) in a panel of human malignant glioma cell lines (U-251MG, U-343MG, LN-229) with stable overexpression of wild-type (IDH1wt) and mutated IDH1 (IDH1R132H). Results Overexpression of IDH1R132H in glioma cells resulted in slightly decreased cell proliferation, considerably reduced cell migration and caused differences in growth properties in 3D spheroid cultures. Furthermore, IDH1R132H-positive cells consistently demonstrated an increased radiosensitivity in human malignant glioma cells U-251MG (DMF10: 1.52, p < 0.01 and 1.42, p < 0.01), U-343MG (DMF10: 1.78, p < 0.01 and 1.75, p < 0.01) and LN-229 (DMF10: 1.41, p < 0.05 and 1.68, p < 0.01) under normoxia and hypoxia, respectively. Conclusion Our data indicate that IDH1R132H mutation causes both a less aggressive biological behavior and direct radiosensitization of human malignant glioma cells. Targeting IDH1 appears to be an attractive approach in combination with radiotherapy.